Use of the «BCR/ABL - multitest» kit in the algorithm of laboratory diagnostics of oncohematological diseases: economic aspects - Gorbenko, A S; Stolyar, M A; Vasiliev, E V; Mikhalev, M A; Bakhtina, V I; Olkhovik, T I; Mochalova, E E; Orlova, K E; Olkhovskiy, I A (Klinicheskaia laboratornaia diagnostika, 2021)
Abnormal mRNAs of the hybrid BCR-ABL gene in the majority of cases initiate the synthesis of proteins with a mass of 210 kDa (p210), 190 kDa (p190), and 230 kDa (p230). Expression of the p210 variant is most common in CML (95% of cases), while the p190 and p230 variants are less common (1-4%). On the contrary, p190 predominates in ALL. Measurement of BCR/ABL gene expression is included in clinical guidelines for the diagnosis of CML and ALL as sequential tests in accordance with their occurrence. At the same time, in the context of primary patients testing with suspected hematological malignancies with a low prevalence of BCR-ABL positive patients in the cohort of examined individuals, sequential testing is associated with low cost-effectiveness. Purpose: approbation of a parallel algorithm for detecting all three (p210, p190 and p230) using the multiplex RT-PCR format implemented in the «BCR/ABL-MULTITEST» reagent kit. We used anonymized blood samples from patients with suspected CML, as well as samples from ALL patients before starting therapy. Testing of blood samples was carried out using two variants of the algorithm: sequential determination of individual BCR-ABL transcripts and parallel determination using the developed set of reagents «BCR/ABL-MULTITEST». To detect the p210 transcript, a commercial kit «AmpliSens® Leukemia Quantum M-bcr-FRT» (Central Research Institute of Epidemiology of Rospotrebnadzor, Russia) was used. Simultaneously, a test was used to detect all three variants of BCR-ABL transcripts using the «BCR/ABL - MULTITEST» reagent kit based on a monochrome multiplex reaction «in one test tube». Reverse transcription were carried out using the REVERTA-L reagent kit (Central Research Institute of Epidemiology of Rospotrebnadzor, Russia) in accordance with the manufacturer's instructions. Using the reagent kits «BCR/ABL-MULTITEST» and «AmpliSens® Leukemia Quantum M-bcr-FRT» there is a high level of correlation of quantitative results of determining the chimeric transcript BCR-ABL р210 (r = 0.99). When using the proposed parallel algorithm with the primary use of the «BCR/ABL-MULTITEST» reagent kit, out of 95 patients with suspected CML, 9 samples with p210 transcript were identified, one with p190 BCR / ABL, and in one case a transcript variant characteristic of chronic neutrophilic leukemia - p230 BCR / ABL. The estimated cost for detecting one positive case of BCR-ABL when using the parallel diagnostic algorithm «BCR/ABL-MULTITEST» with a focused flow of studies is reduced by about 2 times due to a decrease in the amount of laboratory plastic used and the volume of the reaction mixture, as well as the absence of the need for repeated separate tests to detect p190 and p230. The use of the multiplex PCR-RT test system «BCR/ABL-MULTITEST» allows detecting in one test tube all three main variants of BCR-ABL transcripts - p210, p190, p230 and achieving significant resource savings when examining a cohort of patients with suspected CML and ALL and low frequency of positive samples.Abnormal mRNAs of the hybrid BCR-ABL gene in the majority of cases initiate the synthesis of proteins with a mass of 210 kDa (p210), 190 kDa (p190), and 230 kDa (p230). Expression of the p210 variant is most common in CML (95% of cases), while the p190 and p230 variants are less common (1-4%). On the contrary, p190 predominates in ALL. Measurement of BCR/ABL gene expression is included in clinical guidelines for the diagnosis of CML and ALL as sequential tests in accordance with their occurrence. At the same time, in the context of primary patients testing with suspected hematological malignancies with a low prevalence of BCR-ABL positive patients in the cohort of examined individuals, sequential testing is associated with low cost-effectiveness. Purpose: approbation of a parallel algorithm for detecting all three (p210, p190 and p230) using the multiplex RT-PCR format implemented in the «BCR/ABL-MULTITEST» reagent kit. We used anonymized blood samples from patients with suspected CML, as well as samples from ALL patients before starting therapy. Testing of blood samples was carried out using two variants of the algorithm: sequential determination of individual BCR-ABL transcripts and parallel determination using the developed set of reagents «BCR/ABL-MULTITEST». To detect the p210 transcript, a commercial kit «AmpliSens® Leukemia Quantum M-bcr-FRT» (Central Research Institute of Epidemiology of Rospotrebnadzor, Russia) was used. Simultaneously, a test was used to detect all three variants of BCR-ABL transcripts using the «BCR/ABL - MULTITEST» reagent kit based on a monochrome multiplex reaction «in one test tube». Reverse transcription were carried out using the REVERTA-L reagent kit (Central Research Institute of Epidemiology of Rospotrebnadzor, Russia) in accordance with the manufacturer's instructions. Using the reagent kits «BCR/ABL-MULTITEST» and «AmpliSens® Leukemia Quantum M-bcr-FRT» there is a high level of correlation of quantitative results of determining the chimeric transcript BCR-ABL р210 (r = 0.99). When using the proposed parallel algorithm with the primary use of the «BCR/ABL-MULTITEST» reagent kit, out of 95 patients with suspected CML, 9 samples with p210 transcript were identified, one with p190 BCR / ABL, and in one case a transcript variant characteristic of chronic neutrophilic leukemia - p230 BCR / ABL. The estimated cost for detecting one positive case of BCR-ABL when using the parallel diagnostic algorithm «BCR/ABL-MULTITEST» with a focused flow of studies is reduced by about 2 times due to a decrease in the amount of laboratory plastic used and the volume of the reaction mixture, as well as the absence of the need for repeated separate tests to detect p190 and p230. The use of the multiplex PCR-RT test system «BCR/ABL-MULTITEST» allows detecting in one test tube all three main variants of BCR-ABL transcripts - p210, p190, p230 and achieving significant resource savings when examining a cohort of patients with suspected CML and ALL and low frequency of positive samples.